ANALISIS KECERDASAN SPIRITUAL PESERTA DIDIK KELAS X MA AL-MUSTAQIM DESA ARANG LIMBUNG - Elti Melinda; Sri Lestari; Abas Yusuf (Universitas Tanjungpura, 2019)
AbstractThe spiritual intelligence was aperson’s ability to give sense of rites towards their everyday’s behavior and activities through steps and natural tendency – way of thinking, in order to be a completehuman (hanif). And has a tauheed way of thinking (intregralistic) and with a principe of “because of Allah Subhana wata’ala”. The problem in this research was “The Condition of Spiritual Intelligence of the Students of the Tenth Grader of Islamic Senior High School of Al-Mustaqim, In Arang Limbung Village”. The purpose of this research was to understand and acquire the conception on the matter of spiritual intelligence of Islamic senior high school of Al-Mustaqim, in Arang Limbung Village. The method that is used was a descriptive method in the form of study survey research. The samples of this research are 42 students of tenth grader of Islamic senior high school of Al-Mustaqim, in Arang Limbung Village. This research was an indirect communication technique by the tool of collecting data in the form of questionnaire. The technique of data analysis using a percentage calculation. Based on the result of the data analysis, student of Islamic senior high school of Al-Mustaqim for overall, reach 60% in the category of “quite high”. Keywords: Spiritual Intelligence, Al-Mustaqim, Arang Limbung Village